EARLY CHILDHOOD CARIES - EPIDEMIOLOGY, ETIOLOGY, RISK FACTORS, COMPLICATIONS AND PREVENTION - A Kovalčík; P Kamínková; M Miklasová (Czech Dental Chamber, 2024)
Introduction and aim: Dental caries in preschool-age children is a serious problem of modern society with a high prevalence. Early Childhood Caries (ECC) is defined as the presence of one or more cavitated or noncavitated carious lesions, teeth extracted due to caries or teeth treated with filling therapy in children under the age of 71 months. Although it is a preventable disease with known causes, it is the most common chronic disease in children. It substantially affects the quality of life of children and their parents and represents a burden on public health. This condition requires professional care, but it is often left with no therapy. The aim of this review is to summarize the available knowledge on prevalence, etiology, risk factors, complications, and prevention of early childhood caries. Methods: For this review, publications in English and Czech were searched from the databases PubMed, Web of Science, and Medvik using the key words: ECC, early childhood caries, caries in children. Results: The prevalence of ECC remains high despite education and preventive measures. The frequency of untreated ECC and associated complications is also substantial. Conclusion: The issue of early childhood caries is still highly relevant. It is important for both the paediatric dentist and the general dentist to understand the causes of its development and to identify risk factors in the individual patient. Prevention of ECC should start prenatally.